2000
DOI: 10.1590/s0006-87052000000100013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do pH da rizosfera de genótipos de café em resposta à toxidez de alumínio no solo

Abstract: RESUMOFoi realizado um experimento em casa de vegetação com o objetivo de avaliar a relação entre pH da rizosfera e tolerância ao Al de cinco genótipos de café, na presença e na ausência de calagem. As plantas de café foram desenvolvidas em caixas plásticas, com as raízes próximas da tampa. Após 90 dias as tampas foram removidas e uma fina camada de agar contendo indicador foi derramada sobre a superfície. Também foram avaliados a produção de biomassa seca da parte aérea e das raízes, o comprimento e a superfí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…However, with aluminum, there was no alteration. These results suggested that pH variation was dependent on the absence or presence of aluminum in the medium, and that the different cultivars did not interfere in this variation, confirming the results of Braccini et al (2000b). Many studies have shown that root growth inhibition is the most rapid visible symptom of aluminum toxicity in the plants, resulting in root system reduction and injuries, likely leading to mineral deficiency and water stress (Degenhardt et al, 1998).…”
Section: Resultssupporting
confidence: 68%
“…However, with aluminum, there was no alteration. These results suggested that pH variation was dependent on the absence or presence of aluminum in the medium, and that the different cultivars did not interfere in this variation, confirming the results of Braccini et al (2000b). Many studies have shown that root growth inhibition is the most rapid visible symptom of aluminum toxicity in the plants, resulting in root system reduction and injuries, likely leading to mineral deficiency and water stress (Degenhardt et al, 1998).…”
Section: Resultssupporting
confidence: 68%
“…Degenhardt et al (1998) presented the first evidence of an Al-tolerance mechanism based on pH increase in rizosphere of an Arabidopsis thaliana mutant, tolerant to Al toxicity. On the other hand, Braccini et al (2000a) demonstrated that rizosphere pH-changes of coffee plants were not related to higher capacity of this specie to tolerate excess Al in soil. Since the mechanisms to Al toxicity so far have elucidated excluded organic compounds in rizosphere, one may consider that the cultivation of plant materials in the same nutrient solution, as in the present experiment, may influence the plant reaction to Al toxicity.…”
Section: Discussionmentioning
confidence: 84%
“…We can observe that Al at all concentrations affected the initial development of barley seedlings for all parameters evaluated. Under conditions of Al extress, plant tolerance has been associated with the control of pH in the rhizosphere and the exclusion of Al by the plasma membrane of plant roots, as presented by Braccini et al (2000) and Souza et al (2011). The same was observed for the Cu element, except for the PDM parameter, which did not demonstrate a significant difference between the other treatments.…”
Section: Discussionmentioning
confidence: 99%